2020
DOI: 10.1051/0004-6361/202037938
|View full text |Cite
|
Sign up to set email alerts
|

Joint action of Hall and ambipolar effects in 3D magneto-convection simulations of the quiet Sun

Abstract: The partial ionization of the solar plasma causes several nonideal effects such as the ambipolar diffusion, the Hall effect, and the Biermann battery effect. Here we report on the first three-dimensional realistic simulations of solar local dynamo where all three effects were taken into account. The simulations started with a snapshot of already saturated battery-seeded dynamo, where two new series were developed: one with solely ambipolar diffusion and another one also taking into account the Hall term in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…The aim of the current work is to start filling this gap and to provide an initial study of the influence of non-ideal effects on vorticity in realistic three-dimensional simulations of small-scale solar dynamo in the saturated regime. We continue the study from Khomenko et al [34] (Paper I) and González-Morales et al [40] (Paper II) on the action of the ambipolar diffusion and Hall effect in three-dimensional models of solar magneto-convection, with a special emphasis on the vorticity generation and dissipation, and on modifications of the average magnetic structure of the atmosphere due to the Hall effect.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The aim of the current work is to start filling this gap and to provide an initial study of the influence of non-ideal effects on vorticity in realistic three-dimensional simulations of small-scale solar dynamo in the saturated regime. We continue the study from Khomenko et al [34] (Paper I) and González-Morales et al [40] (Paper II) on the action of the ambipolar diffusion and Hall effect in three-dimensional models of solar magneto-convection, with a special emphasis on the vorticity generation and dissipation, and on modifications of the average magnetic structure of the atmosphere due to the Hall effect.…”
Section: Introductionmentioning
confidence: 69%
“…In Paper I and II we split the compressible and incompressible perturbations by computing the divergence and the curl of the velocity field parallel to the magnetic field lines. This separation works well independently of plasma β , and the incompressible perturbation can be associated with Alfvén waves [34,40,51]. The behaviour of Alfvén waves and the vorticity is intimately related [28,52].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The ambipolar diffusion has been studied extensively in the context of chromospheric heating and structure formation, both using the analytical theory or idealized, and even realistic, numerical simulations (see the review by Ballester et al, 2018). It has been shown that ambipolar diffusion allows to dissipate into heat incompressible magnetic waves (e.g., Alfvén waves; Khomenko et al, 2018;González-Morales et al, 2020). Resistive dissipation of Alfvén waves, enhanced through ion-neutral interaction, has been considered by Song and Vasyliūnas (2011); Tu and Song (2013); Shelyag et al (2016), andMartínez-Sykora et al (2016).…”
Section: Wave Heating Of the Large-scale Chromospherementioning
confidence: 99%
“…Gonzalez‐Morales et al. (2020) find that ambipolar diffusion near‐surface battery‐excited dynamo reduces the flux of Alfvén waves generated, whilst the Hall effect substantially enhances chromospheric Alfvén fluxes. Heating aspects of waves in the large‐scale solar chromosphere is discussed in details in Section 4.…”
Section: Magnetohydrodynamic Waves In the Large‐scale Chromospherementioning
confidence: 99%